Female Infertility and Herbal Medicine - L Kashani; S Akhondzadeh (Institue of Medicinal Plants, ACECR, 2017)
The causes of female infertility are multifaceted, and may extend to either of the partners or even both. Indeed, the root issues of infertility can be related to both sexes: approximately 50 percent of infertility is caused by female conditions, while approximately 40 percent is male related. It is also worth noting that in 25 percent of infertile couples both partners will have a fertility problem. Herbs originate from plants and plant extracts from a wide variety of natural resources, including plant leaves, bark, flowers, roots, and fruits and berries. Evidence based herbal medicine may present an effective treatment for female infertility. In this review we present some solid evidence for role of herbal medicine in the treatment of female infertility.